1986
DOI: 10.1021/bi00367a055
|View full text |Cite
|
Sign up to set email alerts
|

Binding of N-linked bovine fetuin glycopeptides to isolated rabbit hepatocytes: Gal/GalNAc hepatic lectin discrimination between Gal.beta.(1,4)GlcNAc and Gal.beta.(1,3)GlcNAc in a triantennary structure

Abstract: Glycopeptides were isolated from bovine fetuin after digestion with Pronase, aminopeptidase M, and carboxypeptidase Y. The glycopeptides were derivatized with tert-butyloxycarbonyltyrosine and separated on the basis of peptide by using reverse-phase high-performance liquid chromatography. Using 400-MHz 1H NMR, the asialotriantennary oligosaccharides at each of the three N-linked glycosylation sites were found to be combinations of the following two structures in which the third branch is either Gal beta(1,4)Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(58 citation statements)
references
References 29 publications
3
55
0
Order By: Relevance
“…Fetuin (Life Technologies, Inc.), which is the major glycoprotein in fetal calf serum (35), has a molecular mass of 48,400 with the following composition: 78% amino acids, 8.7% sialic acid, 6.3% hexosamines, and 8.3% neutral sugars (36). It bears six oligosaccharide side chains/molecule, three of them (of two types) are O-glycosyl-linked to Ser or Thr residues of the protein core, and the other three are N-glycosyl-linked to asparagine (37)(38)(39).…”
Section: Methodsmentioning
confidence: 99%
“…Fetuin (Life Technologies, Inc.), which is the major glycoprotein in fetal calf serum (35), has a molecular mass of 48,400 with the following composition: 78% amino acids, 8.7% sialic acid, 6.3% hexosamines, and 8.3% neutral sugars (36). It bears six oligosaccharide side chains/molecule, three of them (of two types) are O-glycosyl-linked to Ser or Thr residues of the protein core, and the other three are N-glycosyl-linked to asparagine (37)(38)(39).…”
Section: Methodsmentioning
confidence: 99%
“…These analyses clearly demonstrated that an efficient delivery of proteins to hepatocytes by galactosylation can be achieved by adjusting the degree of galactosylation to a value for the distance between two vicinal galactose residues as short as 20-30 Å, which is of the same order as the naturally occurring sugar clusters arranged at the vertices of a triangle with sides of dimensions 15, 22, and 25 Å. 6) A similar pharmacokinetic analysis was applied to the tissue distribution of mannosylated proteins. 18,19) We found that mannosylated proteins bind to serum-type mannan binding protein (MBP) in a structure-dependent manner.…”
mentioning
confidence: 88%
“…5,6) In order to modify proteins as well as other polymers with sugar moieties, monomeric sugar derivatives are suitable because they can be easily synthesized. Experiments using mannosylated bovine serum albumin (Man-BSA) 7) and galactosylated BSA (Gal-BSA) 8) suggest that the number of sugar residues play an important role in recognition by macrophage mannose receptors or asialoglycoprotein receptors, respectively.…”
Section: Pharmacokinetic Considerations Involving Cell-specific Targementioning
confidence: 99%
“…Studies designed to elucidate the structural basis of the biological reactivity of naturally derived carbohydrates frequently require the resolution of complex mixtures of oligosaccharides (usually from glycoproteins) or glycolipids. Separation of oligosaccharides that vary only by a single linkage position is often required to define specificities of antibodies (5, 6), lectins (7,8), and glycosyltransferases (9, 10). We report that high-performance anion-exchange chromatography efficiently resolved positional isomers of oligosaccharides and glycopeptides and coupled to electrochemical detection by pulsed amperometry (HPAE-PAD) (11) allowed detection of both reducing and nonreducing underivatized carbohydrates in the pmol range.…”
Section: Introductionmentioning
confidence: 99%
“…In 2-acetamido-2-deoxypyranosides, the 3-OH is relatively acidic as a result of the acetamido function (27). Pentasaccharides 8 and 9 differ only in that glucose is substituted for GlcNAc in both branches of compound 8. The glucose-containing pentasaccaride had a significantly greater retention time (8.5 min), suggesting that either the 2-OH of glucose is more acidic than the 3-OH of GlcNAc or that the 2-OH of glucose is more accessible to the surface of the pellicular resin.…”
mentioning
confidence: 99%